Iz glasbenega dela Valentina Lechnerja - Špendal, Manica (Muzikološki zbornik, 1989)
The composer Valentin Lechner was working in Maribor as a professional musi-cian f"Musikmeister") from about 1800 to 1805. His preserved, mostly sacred musi-cal pieces would suggest that Lechner must have been an organist at Maribor parish church. The rare pieces ofthe preserved biographic material indicate that Lechnerleft Maribor in 1805 (Jnd took the post oforganist at thecityparish church ofSt. Agydius (sv. Egidij), Klagenfurt/Celovec. The cathedral archives ofMaribor contain two partly and one integrally preserved masses b.y Lechner (handwriting is the same in all three, yet it. cannot be stated with any certainty whether it is Lechner's or belonging to a later copyist). Three masses by V. Lechner are also enteredin the catalogue "Glasbeni rokopisi in tiski na Slovenskem do leta 1800" (Music Manuscripts andPrints in Slove-nia till 1800, publ. 1967). Masses by Lechner are solemn and written for soloists, mixed four-part choir, orchestra, and organ. Additionally, the cathedral archives con-tain Lechner's Easter Song (Osterliedl for CA TB with orchestra accompaniment. The 1967 catalogue mentioned above lists among the manuscripts kept by the Maribor cathedral archives also a Te Deum by Lechner. Another manuscript piece by Lechner preserved outside the Maribor cathedral archives is Tantum ergo kept in the archives of Vordenberg, later published in print as well.
Keywords: glasba; Lechner, Valentin; music